Conflictos por la botica de los jesuitas de Santiago : la expulsión de la orden y el caso de José Zeitler - Eduardo Gutiérrez Ramírez (Nuevo mundo - Mundos Nuevos, 2017)
In Chile, the Society of Jesus, along with its importance as a missionary order, was responsible for delivering a series of services to the vecinos of the cities and towns. In Santiago, the Colegio Máximo de San Miguel became the nerve center of the Jesuit actions: it offered libraries, orchards, teachers and a drugstore. In this article, we analyze the function the drugstore of the Colegio had within the city, and the resolution of the conflict between the King’s order of expulsion of the Jesuits in 1767, and the proper necessities of the city of Santiago, taken in charge by the Jesuit apothecary José Zeitler